Relatório de Estágio Supervisionado. - Oliveira, Renata Ferreira (Universidade Federal do Tocantins, 2023)
The supervised internship report describes the activities carried out at the JBS S / A Company, located in the Municipality of Araguaína -TO, in the Quality Assurance Sector, during the period from September 26 to December 6, 2016. The daily activities carried out in the refrigerator were From the reception of the animals in the corrals to the boarding of the carcasses in cold camera trailers. The quality assurance activities were carried out in several sectors of the company (corral, slaughter, dirty / clean bucharia, kids, and loading), among the activities we monitor the hygienic conditions of the establishment and its employees in order to produce and supply Products to the consumer. In addition, we had basic understanding of quality control, through the Hazard Analysis and Critical Control Point Program - HACCP, Good Manufacturing Practices - GMPs, Standard Operating Procedures – PPHO.